Inclusion, inc. how to design intersectional equity into the workplace - Sanford, Sara (Wiley, 2022)
"Inclusion, Inc tackles the realities of workplace bias and reveals an innovative, proven approach--changing mechanics rather than mindsets--that businesses can adopt today to design bias out and equity in and harness the collective intelligence of their employees. Readers will learn exactly what equity looks like, how to adjust "cultural levers" to create systemic change, and how to avoid common DEI pitfalls that are counterproductive, despite good intentions. This is not a book on personal behaviors. It is an opportunity to plan for equity like any other critical business function, by implementing sustainable, cost-effective solutions that yield measurable returns. Drawing from case studies of GEN-certified organizations, data from thousands of surveys, interviews with executive-level changemakers, and innovations from behavioral economics and design-centered thinking, this book gives readers--employees to executives--tools to counterbias at any level in their organization."--